2018
DOI: 10.15537/smj.2018.8.22337
|View full text |Cite
|
Sign up to set email alerts
|

Orthodontic treatment needs in Saudi young adults and manpower requirements

Abstract: Objectives:To evaluate orthodontic treatment needs using the index of orthodontic treatment need (IOTN) components and to estimate the required manpower in the city of Jeddah, Saudi Arabia.Methods:A cross-sectional study involving 670 participants (390 females and 280 males) collected between November 2016 and April 2017, whose ages ranged from 12-19 years from secondary and high school students. Treatment needs were estimated using the IOTN components, dental health component (DHC), and aesthetic component (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
31
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 19 publications
5
31
2
1
Order By: Relevance
“…Recent research in the north of the country showed 52.8% class I malocclusion among adolescents. [11] The same research also found the following prevalence for other features: overbite (23.4%), excessive overjet (22.2%), reduced overbite (12.2%), and open bite (4.6%). [8]…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…Recent research in the north of the country showed 52.8% class I malocclusion among adolescents. [11] The same research also found the following prevalence for other features: overbite (23.4%), excessive overjet (22.2%), reduced overbite (12.2%), and open bite (4.6%). [8]…”
Section: Introductionmentioning
confidence: 81%
“…[8] Nonetheless, few reports exist that explore the malocclusion prevalence in Saudi Arabia. [910111213] Malocclusion prevalence was found by Al-Emran et al . to be 62.4% for Saudi children, 40% of whom required fixed orthodontic devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the patient's understanding of the need for treatment or an aesthetic classification is not the same as therapists it can pose a problem, in the sense of the constraints of the need for therapy or it may complicate the therapy it self [28,33]. Although for efficient orthodontic treatment must take into consideration the perception of the patient, not just the professional assessment of the therapist in order to ensure patient satisfaction.…”
Section: R P Nmentioning
confidence: 99%
“…Because malocclusion can affect a patient’s function and appearance, it is better if it is identified and treated at early stages to avoid further complications [15] and to increase the probability of a favourable prognosis [16]. Unfortunately, few studies have examined the prevalence of malocclusion in the western region of Saudi Arabia [17], [18]. Further studies in the western region would form a complete database to aid in planning appropriate orthodontic treatment services among all regions of Saudi Arabia and help to assess the resources needed to overcome the increasing number of malocclusion cases.…”
Section: Introductionmentioning
confidence: 99%